Manajemen Peserta Didik dalam Pengembangan Bakat dan Minat Siswa melalui Kegiatan Ekstrakurikuler di SD Istiqomah Bandung - Kinesti, Rakanita Dyah Ayu; Arviansari, Nadia Ariella; Syafi’atulkhoir, Salsabila; Azizah, Nurul; Sani, Choirun Nisa Nur; Rizqia, Laili Fitri (YASIN, 2022)
SD Istiqomah Bandung is one of the leading elementary schools in the city of Bandung. This predicate was obtained by SD Istiqomah based on what has been achieved, especially in the extracurricular field. This is supported by a very supportive teaching staff, budget, and infrastructure. This study aims to determine the planning (planning), organizing (organizing), implementation (actuating), and monitoring (controlling) the management of students in developing their interests and talents through extracurricular activities at SD Istiqomah Bandung. This study used descriptive qualitative method. The resource persons for this study were the extracurricular supervisor, the vice principal for student affairs, and the principal of SD Istiqomah Bandung. The technique for collecting data uses observation techniques, observations, focus groups, notes obtained in the field, and documentation taken with research instruments in the form of observation sheets and audio visuals. In this study, after carrying out the determination of the technique in collecting data, the research team carried out the preparation of the instruments that were arranged according to the research indicators. Observations were carried out once, the observations and focus groups lasted about three hours. The research location is SD Istiqomah Bandung. The result of this research is to provide knowledge about student management in developing their interests and talents through extracurricular activities at SD Istiqomah Bandung.